2006
DOI: 10.1186/1475-9276-5-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high up front charges on access to surgery for poor patients at a public hospital in New Mexico

Abstract: BackgroundA public hospital in New Mexico required collection of 50% of estimated costs prior to elective surgeries for self-pay patients. This study assesses the impact of this policy on access to elective surgical procedures.MethodsChi-square tests determined if there was a statistically significant difference between the number of self-pay and insured patient cancellations for financial reasons. A multivariate binomial regression model was used to calculate risk ratios and confidence limits for effects of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, the positive impact of health insurance on increasing use of PCC facilities has been shown in several studies. [ 23 25 33 ] In this study, midwives and gynecologists provided 15.9% and 64.5% of PCC, respectively. Mastroiacovo et al .…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the positive impact of health insurance on increasing use of PCC facilities has been shown in several studies. [ 23 25 33 ] In this study, midwives and gynecologists provided 15.9% and 64.5% of PCC, respectively. Mastroiacovo et al .…”
Section: Discussionmentioning
confidence: 93%
“…In a study conducted by Kaufman et al it was found that patients who pay for their treatment themselves are more likely to cancel their surgery than those who are insured (39). Therefore, if government and private sector support is provided for the whole community through expanding insurance coverage, access to health care services will be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Since most low-income immigrant patients were not able to pay 50% out of pocket, either they did not access care or they experienced limited access. For instance, a study 8 assessing the impact of the financial assistance policy on undocumented immigrant patients found that compared to those with insurance, the majority (56% vs. 9%) had their recommended elective surgeries cancelled, presumably because they couldn’t afford the 50% up-front payment required of those who are uninsured and not in the UNM Care Program.…”
Section: The Tension Among Service Delivery Policy and Medical Educmentioning
confidence: 99%